UJI VALIDITAS DAN RELIABILITAS KUESIONER THE 15ITEM MYASTHENIA GRAVIS QUALITY OF LIFE SCALE VERSI BAHASA INDONESIA MGQOL15 INA - Ahmad Yanuar Safri* Fitri Octaviana,* Fikry Syahrial,* Luh Ari Indrawati,* Winnugroho Wiratman,* Man (Neurona Majalah Kedokteran Neuro Sains, 2020)
INTRODUCTION MYASTHENIA GRAVIS MG IS A CHRONIC AUTOIMMUNE DISEASE IN THE NEUROMUSCULAR JUNCTION CHARACTERIZED WITH FLUCTUATING WEAKNESS SYMPTOMS ADVANCE IN THE DIAGNOSIS AND MANAGEMENT OF MG CASES INCREASES THE PATIENTS LIFE EXPECTANCY THEREFORE THE EVALUATION OF THERAPEUTIC SUCCESS IS NO LONGER BASED SOLELY ON COPING WITH THE SYMPTOMS BUT ALSO IN EVALUATING THE QUALITY OF LIFE OF PATIENTS THE 15ITEM MYASTHENIA GRAVIS QUALITY OF LIFE SCALE MGQOL15 IS A QUESTIONNAIRE UTILIZED TODAY TO EVALUATE THE QUALITY OF LIFE OF MG PATIENTS